Improving care for individuals with serious infections who inject drugs. (December 2022) - Kershaw, Colleen; Lurie, Jon D; Brackett, Charles; Loukas, Elias; Smith, Katie; Mullins, Sarah; Gooley, Christine; Borrows, Melissa; Bardach, Shoshana; Perry, Amanda; Carpenter-Song, Elizabeth; Landsman, H. Samuel; et al.
Background: Hospitalizations for serious infections requiring long-term intravenous (IV) antimicrobials related to injection drug use have risen sharply over the last decade. At our rural tertiary care center, opportunities for treatment of underlying substance use disorders were often missed during these hospital admissions. Once medically stable, home IV antimicrobial therapy has not traditionally been offered to this patient population due to theoretical concerns about misuse of long-term IV catheters, leading to discharges with suboptimal treatment regimens, lengthy hospital stays, or care that is incongruent with patient goals and preferences. Methods: A multidisciplinary group of clinicians and patients set out to redesign and improve care for this patient population through a health care innovation process, with a focus on increasing the proportion of patients who may be discharged on home IV therapy. Baseline assessment of current experience was established through retrospective chart review and extensive stakeholder analysis. The innovation process was based in design thinking and facilitated by a health care delivery improvement incubator. Results: The components of the resulting intervention included early identification of hospitalized people who inject drugs with serious infections, a proactive psychiatry consultation service for addiction management for all patients, a multidisciplinary care conference to support decision making around treatment options for infection and substance use, and care coordination/navigation in the outpatient setting with a substance use peer recovery coach and infectious disease nurse for patients discharged on home IV antimicrobials. Patients discharged on home IV therapy followed routine outpatient parenteral antimicrobial therapy (OPAT) protocols and treatment protocols for addiction with their chosen provider. Conclusion: An intervention developed through a design-thinking-based health care redesign process improved patient-centered care for people with serious infections who inject drugs.